Optimasi Konversi Daya Turbin Angin Melalui Pengaturan Tsr (Tip Speed Ratio) dan Jenis Turbin - Reynaldi Aurel Fadiilah; Mardi Santoso; Mohammad Abu Jami'in; George Endri Kusuma; Didik Sukoco (Proceedings Conference on Marine Engineering and its Application, 2023)
Society is very dependent on fossil fuels, and currently Indonesia does not haveexcess oil reserves. According to the DEN, oil reserves will be exhausted in the next nineyears. As an alternative, wind turbines can be used. However, the factor hindering thisdeployment is the design of the wind turbines, which is lacking. MPPT is used in windturbines to optimize performance by determining the state of the wind turbine, thencalculating the power sampling algorithm, and then calculating the overall performance andefficiency of the wind turbine. State 1, Vci 1 m/s, Vr 6 m/s, and Vco 8 m/s provide the highestpower of the three. The H_Single Cp 0.47 and Tsr 4.5 turbines with a ratio of one rotor aresuitable for use in several areas on the island of Java. If you want a greater output powerfrom a wind turbine, then you can use a turbine with dual rotors, namely the HCR turbine,because it is capable of producing almost twice as much as a turbine with one rotor. Thearea with the most potential to generate electricity is in the Tuban area. Overall efficiencywith a maglev wind generator (model WKG-1000-200r) gives a Savonius efficiency of 18.2%,an H-Darrieus efficiency of 22.1%, an HCR efficiency of 63%, and an H-Single efficiency of42.3%.